La educación sexual infantil para desarrollar la identidad y autonomía de los niños y niñas de 4-5 años de la escuela Alonso de Mercadillo de la ciudad de Loja, periodo septiembre 2013-julio 2014 - Camacho Curimilma, Yessenia Liliana (2015)
Thepresent researchcalled. EDUCATIONTO DEVELOPCHILD SEXUALIDENTITY ANDAUTONOMYOFCHILDREN4-5 YEARSOFSCHOOLALONSODEMARKETCITYLoja, PERIODSEPTEMBER2013-JULY 2014.Its objectives: determinethe theoretical foundationofSex Educationandchildren'sIdentity andAutonomy ofchildren4-5years old.Identifythe problems of identityand autonomy thathavechildren4-5years ofMarketAlonsoSchoolofLoja. Develop aguide toChildSexualEducationto developthe identityand autonomy ofchildren4-5years ofMarketAlonsoofschool.Applythe guidance ofChildSexualEducationfor use in developingtheidentity andautonomy ofchildren aged4-5 years.Validatethe relevanceguideChildSexualEducationto develop theidentity andautonomyofchildren4-5years old. Analytic, descriptive, hermeneutic-dialectic, inductiveand statistical: To carry outresearchmethods were used. The techniques usedaredirectedto the teacherinterview, the surveymothers, observation sheetfor children. Oncethe results were obtainedwas evidentthat children/ asdid not havea propersexualeducation,the mothers, the teacher did not have theappropriate skillsto carry outthetraining process.Itis recommendedthatboththe teacher andthemothers whoarethe prime moversineducating children/ asina healthy sexeducationtochildrenin this way/ asfeel confidentand happyidentitythemselves.